Pengembangan UMKM pada Destinasi Wisata Kecamatan Cimenyan Kabupaten Bandung - Rosmery Elsye (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
This research aims to find out the development of tourism objects which have an impact to Small Micro Medium Enterprises (SMMEs) in Cimenyan District, Bandung. The method used in this research is qualitative with descriptive analysis. The data used in this research are primary and secondary data. The primary data are obtained from field observation and interviews, while the secondary data are obtained from literature, documentations, and laws and regulations related to tourist destination, SMMEs and traditional food. The result shows that the development of tourist destination is in accordance with the current tourism potential. It can be concluded that with a good infrastructure to the destination, it will make more tourist come and affect to the growth of SMMEs in Cimenyan District and the surrounding area, Bandung.